ANALISIS PEMBELAJARAN PENDIDIKAN KARAKTER DISIPLIN DI SD NEGERI NEGLA - Listin Lia; Cece Rakhmat; Fajar Nugraha (PIWURUK: Jurnal Sekolah Dasar, 2021)
Abstract: This study aims to describe the profile of disciplinary character habituation and aspects of discipline character education for grade 5 at SDN Negla. This study used a qualitative descriptive approach with research subjects, namely grade 5 students at SDN Negla with data collection techniques in the form of interviews, observation, documentation, and questionnaires. The results showed that the profile of disciplinary character education habituation at SDN Negla has an average score of 54.9 (including the criteria, "Poor"). The aspects of the character of student discipline include time discipline with indicators of obedience to learning activities and adherence to punctuality at school, discipline in enforcing rules with indicators of obedience to school discipline, attitude discipline with indicators of praying when doing activities, saying greetings, shaking hands with elders. , disposing of garbage in its place, getting along well with friends, and the behavior and disciplinary aspects of learning with indicators of the method being taught and classroom management. The results showed that each aspect had a different value. As many as 9.8% of the discipline aspects of time are in sufficient criteria, 24% of disciplinary aspects of enforcing rules are in sufficient criteria, as many as 8.4% of aspects of discipline of learning are in sufficient criteria, and 61.4% are aspects of discipline of attitudes that are in the criteria less. The discipline aspect of students at SD Negeri Negla, with the highest number of disciplinary attitudes as much as 61.4%, is a poor criterion.Keywords: Learning; Discipline Character Education.Â Abstrak: Penelitian ini bertujuan untuk mendeskripsikan profil pembiasaan karakter disiplin dan aspek pendidikan karakter disiplin kelas 5 di SDN Negla. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan subjek penelitian yaitu siswa kelas 5 di SDN Negla dengan teknik pengumpulan data berupa wawanara, observasi, dokumentasi, dan angket. Hasil penelitian menunjukan bahwa profil pembiasaan pendidikan karakter disiplin di SDN Negla memiliki nilai rata-rata 54,9 (termasuk kriteria, â€œKurangâ€). Adapun aspek karakter disiplin siswaÂ  meliputi kedisiplinan waktu dengan indikator ketaatan terhadap kegiatan belajar dan ketaatan terhadap ketepatan waktu di sekolah, kedisiplinan menegakan aturanÂ  dengan indikator ketaatan terhadap tata tertib di sekolah, kedisiplinan sikap dengan indikator berdoa ketika beraktifitas, mengucapkan salam, bersalaman dengan yang lebih tua, membuang sampah pada tempatnya, rukun bersama teman, danÂ  perilaku serta aspek kedisiplinan pembelajaranÂ  dengan indikator metoda yang diajarkan dan pengelolaan kelas. Hasil penelitian menunjukkan masing â€“ masing aspek memiliki nilai yang berbeda. Sebanyak 9,8% aspek kedisiplinan waktu berada dalam kriteria cukup, sebanyak 24% aspek kedisiplinan menegakan aturan berada dalam ktiteria cukup, sebanyak 8,4% aspek kedisiplinan pembelajaran berada dalam kriteria cukup, dan 61,4% merupakan aspek kedisiplinan sikap berada dalam kriteria kurang. Aspek kedisiplinan siswa di SD Negeri Negla yang jumlahnya paling banyak adalah kedisiplinan sikap sebanyak 61,4% merupakan kriteria kurang.Kata kunci: Pembelajaran; Pendidikan Karakter Disiplin.